The Register of the Qadi Court “Kiyahi Pĕqih Najmuddin” of the Sultanate of Banten, 1754-1756 CE. - Ayang Utriza Yakin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
The present study focuses on manuscript LOr 5626 from the archives of the Qadi of the Sultanate of Bantěn (1527-1813), in Indonesia. This codex is preserved in the Leiden University library, which acquired it from C. Snouck Hurgronje. It consists of the ‘legal cases’ brought before the Kiyahi Pěqih Najmuddin, the Islamic judge in Bantěn, by the inhabitants. The register, which covers the period from 1754 to 1756, is the oldest ‘sijill’ (court record) in Southeast Asia, and it contains cases on marriage, divorce, inheritance, litigation, private transactions, loans, debts, and violence. The manuscript demonstrates the judicial practice exercised by the qadi of Banten and reveals important findings on the relationship between Islamic legal theory and practice This essay hopefully will contribute to Islamic legal history in general both by providing textual evidence that the qadi record (sijill) existed in Southeast Asia during the eighteenth century and by presenting its contents.DOI: 10.15408/sdi.v22i3.2354